IPTEKS PROSEDUR PERENCANAAN KEUANGAN DINAS PERINDUSTRIAN DAN PERDAGANGAN DAERAH PROVINSI SULAWESI UTARA - Kasakeyan, Bella A.; Balo, Daiyana N.; Pattimahu, Dewarti M.M.; Sinaga, Feren L.; Karamoy, Herman (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Regional Finance are all rights and obligations in the framework regions of regional governance that can be valued in money includes all forms of property-related rights and obligations of the area. Regional financial planning needs to be clearly arranged and in accordance with established procedures so that the budget received can be managed properly. By analyzing the financial planning procedures performed Department of Industry and Commerce of North Sulawesi Province in accordance with the Indonesian Government Regulation Nomor 58 of 2005 concerning Management of Regional Finance.Keywords : procedures, planning, regional finance